Přístupy ke zvládání rizik v logistice - Macurová, Pavla; Minárová, Alena; Dejnega, Oleg (Univerzita Pardubice, 2011)
The article is focused on the approaches and particular measures for treatment with risks in logistics. The increasing needs to insure the robustness of supply chains by collaboration of all participants and by including the flexibility into these chains are emphasized and relevant actions are specified. Later, the steps and results of questionnaire survey concerning the treatment with risks in chosen companies in the Czech Republic are presented. In the research the own classification of treatment with risks were suggested and implemented. The classification is based on differences in approaches according to extent of collaboration and potentials for more essential overcoming the variability. Also the level of standardization of the procedures in treatment with risks was searched. The extending of particular approaches to risk was analyzed by statistical techniques, their levels were compared and the conclusions about recognized portfolio of approaches were formulated. In the end the recommendations for next research were suggested.
Keywords: risks in logistics; supply chain risk management; risk mitigation; approaches to treatment with risks; flexibility; empirical survey